Local knowledge and derived practices of safety during pregnancy, childbirth and postpartum: a qualitative study among nurse-midwives in urban eastern Tanzania. Issue 12 (15th December 2022) - Mwakawanga, Dorkasi L; Mwilike, Beatrice; Kaneko, Morie; Shimpuku, Yoko
Abstract : Background: Maternal and newborn mortality are still high in low-income and middle-income countries despite global efforts to improve the quality of care by prioritising evidence-based practices and increasing the number of births attended by skilled personnel. During childbirth, women are hesitant to use the health facility services. Concerns about safety and risks during pregnancy, childbirth and postpartum period are deeply rooted in local health practices and beliefs. Objective: The aim of this study was to explore the perceptions of local health knowledge and derived practices among nurse-midwives in urban eastern Tanzania. Methods: An exploratory qualitative study design was carried out in a district hospital in eastern Tanzania. Twenty-one nurse-midwives participated in two focus group discussions. The data were analysed using qualitative content analysis. Results: Based on existing scientific data, local knowledge and derived practices were categorised as potentially beneficial, neither beneficial nor harmful and potentially harmful. Our study identified a wide range of local knowledge and derived practices used by women. These include to refrain from shouting or crying to prevent exhaustion during labour, drinks and foods restrictions during labour and after birth, and use of local herbs to stimulate labour. In addition, midwives reinforced the importance of integrating local knowledge and practices with potential benefits with evidence-based practices. Encouraging and listening to women would offer an opportunity to reduce harmful practices. Conclusions: While non-harmful and beneficial practices for ensuring safety during pregnancy, childbirth and postpartum period should be accepted and supported as a part of our cultural richness, harmful practices should be discouraged. This can be achieved through antenatal health education and afterbirth health messages on hospital discharge to promote positive childbirth health outcomes.